structural relations among maternal parenting style, self-esteem and depression in adolescents - Baharudin, Rozumah; Zulkefly, Nor Sheereen; Ho, Meng Chuan (2014)
The way parents interact with their child would influence the child’s psychological outcomes. Compared to fathers, mothers are often reported to interact more with their child and presumably have greater impact on the child.Using Structural Equation Modeling, this study aims to explore mothers’ parenting style and how it relates to self-esteem and depression of adolescents.A total of 705 school-going adolescents (mean age = 16.1 years) from the state of Johor completed a self-administered questionnaire measuring parenting style, self-esteem and depression. Results from the structural analysis suggested that maternal authoritative parenting style appear to have a larger influence on adolescents’ self-esteem compared to maternal authoritarian and permissive parenting style.Additionally, findings revealed that only authoritative parenting style had a significant and direct relationships with adolescent depression.On the other hand, authoritarian and permissive parenting styles were found to have indirect relationships to depression via self-esteem. However, authoritative parenting style had an even larger indirect relationship to depression compared to authoritarian and permissive parenting styles.As expected, self-esteem was found to have a significant and negative relationship with depression. Findings suggest that authoritative parenting style is significantly essential in fostering positive psychological outcomes.Programs aimed at promoting positive developmental and psychological outcomes in adolescents, should focus more on the parent-child relationship as family is an important foundation for adolescent development.